Land use/land cover change detection using geospatial techniques in Kupti watershed of Darwha block of Yavatmal district, Maharashtra - PATANGRAY, A. J.; PATIL, N. G.; SINGH, S. K.; MISHRA, V. N.; REDDY, C. V. P.; RAMTEKE, I. K. (Journal of Soil and Water Conservation, 2020)
Land resources in India are under severe pressure and it is widely believed that marginal lands are being brought under plough. The extent of such changes needs to be known for better land use planning decisions. Land use/land cover changes over the period of 15 years (2000 to 2016) were analysed using geospatial techniques in Kupti watershed of Darwha block of Yavatmal district in Maharashtra. The comparison of each class of study over these years showed a significant change in land use and land cover. The ground realities of changes and impact of those changes were verified and ascertained respectively through field observations and site-specific interviews. During 2000 and 2005 period, the per cent area in agriculture class got decreased by 2.2 per cent in the watershed. The second class decrement in all study years was the wasteland area (709 ha) in base year, it was constantly decreasing and now 493 ha in 2016 as it was converted to agriculture land mainly due to encroachment by the farmers or by habitation (49 ha increased from 2000 to 2016). Further, nearly 246 ha of area of waterbody in the watershed got increased during 2000 to 2005. An increase in the forest cover (8 ha) was found in the watershed over 2285 ha within 15 years. Run-off computations also reflected the LULC changes. These findings will help in deciding land use policy for future and its impact on runoff generated from the watershed.